Assessment of a smart concept for d15 shear piezoceramic direct torsion actuation - Benjeddou, Ayech (European Journal of Computational Mechanics, 2011)
An experimentally proved smart concept for piezoceramic direct torsion actuation is here numerically assessed with regards to the bonding and segmentation influence on its behavior and performance. The TRESCA and deflection criteria analysis indicates that the actuator sandwiching with composites contributes to its integrity enhancement, but in the cost of its performance reduction. It is also found that modeling the core inter-rows and composites inter-layers bonding is more influential than that of the core rows segmentation. The conducted open-circuit modal analysis confirms that the inter-rows adhesive softens the actuator, while the inter-layers one stiffens it. Besides, the conducted adhesive parametric analysis indicates that, as expected, the most influential bonding parameters are its thickness and shear modulus.